ANALISIS REJECT FILM DIGITAL RADIOGRAFI DI INSTALASI RADIOLOGI RSUD SIDOARJO BARAT - Akmal Fajar Huwolo; Ari Anggraeni; Ildsa Maulidya Mar'athus Nasokha (Bajang Institute, 2025)
Background: Reject analysis is an evaluation of rejected radiographic results. At the Radiology Department of Sidoarjo Barat General Hospital, the recording and evaluation of rejected films have not been optimally implemented despite the use of Digital Radiography (DR) technology. There are still radiographs that are rejected without adequate documentation and analysis. This study aims to identify the causes of rejection, the percentage of rejected films, and the recording and analysis systems in place. Method: The study was conducted from October 2024 to July 2025 using a mixed-method approach (qualitative and quantitative). The qualitative approach involved observation, interviews, and documentation of radiographers and medical physicists, as well as analysis of secondary data from regulations and publications. The quantitative approach involved collecting data on the total number of digital images and rejected images. The rejection rate was calculated using the formula: (number of rejected images ÷ total number of images) × 100%. Results: The film rejection rate was recorded at 0.84% (8 films out of 946 uses) in October 2024 and increased to 1.96% (23 films out of 1,173 uses) in November 2024, and 1.28% (13 films out of 1,012 uses) in December 2024. The total number of film uses from October to December was 3,131 films. The causes of film rejection included human error (2.72%), tool error (3.86%), foreign objects (0.90%), fog (0.68%), and patient error (1.81%). Tool error was the most common cause. The most common type of examination with rejections was lumbosacral, while the lowest was femur. Conclusion: The implementation of data collection on the factors causing film rejections does not yet comply with regulations. The researcher recommends paying attention to the evaluation of film rejection analysis in radiology department management to ensure quality assurance continues to operate safely